Cancer-related Mutations with Local or Long-range Effects on an Allosteric Loop of p53. Issue 17 (15th September 2022) - Degn, Kristine; Beltrame, Ludovica; Dahl Hede, Freja; Sora, Valentina; Nicolaci, Vincenzo; Vabistsevits, Marina; Schmiegelow, Kjeld; Wadt, Karin; Tiberti, Matteo; Lambrughi, Matteo; Papaleo, Elena
Graphical abstract: Highlights: Conformational alterations of p53 stem from domain mutations and allostery. We studied 1132 reported cancer mutations using structure-based methods. Multi-tier approach with different methods providing different readouts. 43 mutations were predicted to impact protein functionality locally. 6 mutations were predicted to impact the functional interface allosterically. Abstract: The tumor protein 53 (p53) is involved in transcription-dependent and independent processes. Several p53 variants related to cancer have been found to impact protein stability. Other variants, on the contrary, might have little impact on structural stability and have local or long-range effects on the p53 interactome. Our group previously identified a loop in the DNA binding domain (DBD) of p53 (residues 207–213) which can recruit different interactors. Experimental structures of p53 in complex with other proteins strengthen the importance of this interface for protein–protein interactions. We here characterized with structure-based approaches somatic and germline variants of p53 which could have a marginal effect in terms of stability and act locally or allosterically on the region 207–213 with consequences on the cytosolic functions of this protein. To this goal, we studied 1132 variants in the p53 DBD with structure-based approaches, accounting also for protein dynamics. We focused on variants predicted with marginal effects on structural stability. We then investigated each of these variants for their impact on DNA binding, dimerization of the p53 DBD, and intramolecular contacts with the 207–213 region. Furthermore, we identified variants that could modulate long-range the conformation of the region 207–213 using a coarse-grain model for allostery and all-atom molecular dynamics simulations. Our predictions have been further validated using enhanced sampling methods for 15 variants. The methodologies used in this study could be more broadly applied to other p53 variants or cases where conformational changes of loop regions are essential in the function of disease-related proteins.